Mathematics Anxiety and Metacognitive Skills: An Analysis of the Relationship among Junior High School Students - Sukriyah, Dewi; cholella, Alifvita Nur; nuriyatin, siti (Universitas PGRI Semarang, 2026)
This study aims to determine the relationship between mathematical anxiety and the metacognitive skills of eighth-grade students in linear equation material. This is based on the importance of metacognitive skills in supporting mathematical understanding and problem solving, as well as the influence of anxiety as an affective factor that can inhibit the thinking process. This study used a quantitative approach with a one-shot case study design. The research subjects were 23 eighth grade students at SMP Islam Parlaungan who were selected through purposive random sampling. Data collection was conducted through a mathematics anxiety questionnaire, descriptive tests, and interviews on metacognitive skills. Data analysis used Pearson's correlation test, preceded by normality and linearity tests with the assistance of SPSS. The results showed a weak positive and insignificant relationship between mathematics anxiety and students' metacognitive skills, with a correlation coefficient of 0.303 and a significance value of 0.160. It was also found that some students with high anxiety actually demonstrated good metacognitive skills. This indicates that the relationship between the two variables is not linear and may be influenced by other factors. This study suggests the need for a learning approach that supports students' emotional regulation and reflective thinking skills.